Bioecological aspect of lamasi (Barbonymus gonionotus) in mailil rever labuhanbatu district, indonesia - Nur Asia Nasution; Rusdi Machrizal (JPBIO (Jurnal Pendidikan Biologi), 2021)
The existence of gold mining activities in mailil river can disrupt the stability of the ecosystem, fishing by using toxins, which may result in a decrease in fish populations in the river mailil. This study aims to obtain information related to biological and ecological aspects (Barbonymus gonionotus) in river Mailil, Village. This study was conducted from November 2020 to January 2021. The locations for sampling were determined based on information from the local community in Bandar Kumbul Village. Samples were caught using nets, traps, and nets Sampling was conducted from 09:00 am to 03:00 pm. The biological aspect being measured was the length-weight relationship of the fish using the linear allometric model (LAM). Meanwhile, the ecological aspect being measured was the condition factor using Fulton’s K equation and relative weight (Wr) equation. In this study, 54 silver barbs (B. gonionotus) were successfully caught as samples. The results of the length-weight relationship analysis indicated a negative allometric relationship with the value of b = 0.52 (b < 3). Furthermore, the value of Fulton’s K condition factor was 27.75, while the value of relative weight (Wr) condition factor was 100.07. These results indicated that river Mailil as an ecosystem and habitat of silver barbs is in the balance condition.Keywords: Length-weight relationship, Barbonymus gonionotus, aek mailil